Penanganan Masalah Pertanahan Berdasarkan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 21 Tahun 2020 tentang Penanganan dan Penyelesaian Kasus Pertanahan - Awang Hardian Sadono (Universitas Ngudi Waluyo, 2023)
Land issues are problems that often cause prolonged disputes in the dynamics of Indonesian people's lives. The government's efforts to be serious in minimizing or suppressing land disputes are evidenced by the function of handling land cases at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency which then issued a policy related to handling land cases which until its last amendment was through the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of Agency National Land Affairs Number 21 of 2020 Concerning Handling and Settlement of Land Cases. The handling of land cases carried out by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency is a new breakthrough in order to avoid the accumulation of cases in the world of justice. This research aims to examine and analyze the process of handling land cases carried out by the Ministry of Agrarian and Spatial Planning/National Land Agency according to the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 21 of 2020 concerning Handling and Settlement of Land Cases, and to understand and analyze the form of implementation of the cancellation of legal products in handling land cases. From the results of the research it can be stated that the process of handling land cases in relation to the cancellation of Land Rights Certificates can be carried out through the judiciary and outside the court which contains administrative defects and/or juridical defects. Abstrak Masalah Pertanahan merupakan masalah yang sering kali menimbulkan sengketa yang berkepanjangan dalam dinamika kehidupan masyarakat Indonesia. Usaha pemerintah untuk serius dalam meminimalkan atau meredam sengketa pertanahan dibuktikan dengan adanya fungsi penanganan kasus pertanahan pada Kementerian Agraria Dan Tata Ruang/Badan Pertanahan Nasional yang kemudian dikeluarkan kebijakan terkait penanganan kasus pertanahan yang sampai dengan perubahan terakhirnya melalui Peraturan Menteri Agraria Dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 21 Tahun 2020 Tentang Penanganan dan Penyelesaian Kasus Pertanahan. Penanganan kasus pertanahan yang dilakukan oleh Kementerian Agraria Dan Tata Ruang/Badan Pertanahan Nasional adalah merupakan terobosan baru dalam rangka untuk menghindari penumpukan perkara di dunia peradilan. Penelelitian ini bertujuan untuk mengkaji dan menganalis proses penanganan kasus pertanahan yang dilakukan oleh Kementerian Agraria Dan Tata Ruang/Badan Pertanahan Nasional menurut Peraturan Menteri Agraria Dan Tata Ruang/Kepala Badan Pertanahan Nasional Nomor 21 Tahun 2020 Tentang Penanganan dan Penyelesaian Kasus Pertanahan, dan untuk memahami dan menganalisis bentuk pelaksanaan pembatalan produk hukum dalam penanganan kasus pertanahan. Dari hasil penelitian dapat dikemukakan bahwa proses penanganan kasus pertanahan dalam kaitannya dengan pembatalan Sertipikat Hak Atas Tanah dapat dilakukan melalui Lembaga peradilan dan di luar pengadilan yang mengandung cacat adminitrasi dan/atau cacat yuridis.